Organizational Citizenship Behavior (OCB) Ditinjau dari Persepsi Karyawan Tetap Instansi Pemerintah terhadap Gaya Kepemimpinan Transformasional Atasan - Reny Yuniasanti (University of Merdeka Malang, 2014)
Permanent employees in government institution in several decades and until now there are many people who doubt their performance. This study aims to find positive relationship between Organizational Citizenship Behavior (OCB) with the perception of transformational leadership style on permanent employees in government institutions. Subjects in this study were employees of Leather Technology Academy of Yogyakarta, which is collected by random sampling with 30 people. Methods of data collection in this study used a perception of transformational leadership style and Organizational Citizenship Behavior scale (OCB). The data analysis method used Pearson Product Moment analysis. The results of the data analysis results obtained by correlation of rxy = 0.548 and a significance level of 0.000 (p 0.01) indicate that there is significant positive relationship between Organizational Citizenship Behavior (OCB) with the perception of transformational leadership style and has effective contribution 30%.